DEVELOPMENT OF THE SYSTEM OF CONTINUOUS EDUCATION AS A DRIVER OF THE FORMATION OF THE COMPETITIVE HUMAN CAPITAL OF UKRAINE - Takhtarova , K. A.; Chernova , A. M. (The actual problems of regional economy development, 2024)
The article is aimed at researching the system of continuous education in Ukraine and determining ways of its development. Continuity of learning is considered the basis of human formation as a competitive human capital. Through the creation and development of the system of continuous education, a person needs to be given academic freedom in order to be able to independently choose the direction, methods, strategies, methods and means of learning in order to adapt to changes in society and the labor market. The purpose of the study is to improve the theoretical and methodological foundations of the continuous education system as a priority direction in meeting the needs of the labor market in qualified personnel. During the research, dialectical and abstract-logical methods, observation, analysis, synthesis, methods of the system approach were used to classify factors affecting the formation and development of the continuous education system; method of theoretical modeling. According to the task, the materials of the conducted research can provide an opportunity for further study of aspects of the development of the domestic system of continuous education as a factor in the post-war stabilization of the labor market of Ukraine. The article highlights theoretical approaches to the development of human capital, the formation of a system of continuous learning and professional training, because lifelong learning is a complex category and can be considered from different points of view. The development of the system of continuous education in Ukraine is an important task both at the state level and at the level of corporations and enterprises. Continuous learning is essential because it allows individuals to adapt to changes in the labor market, develop new skills and maintain competitiveness in today's world, where technology and requirements change rapidly. Continuous learning promotes creativity, expands horizons and cognitive skills and helps in solving global challenges. The scientific novelty of the obtained results: by summarizing the main trends of the development of the domestic system of continuous learning, a structural-logical model of the system of continuous learning in Ukraine was developed, in which it is presented as a set of interdependent elements created for the formation of competitive human capital to ensure the economic and social progress of society. In practical application, this can contribute to effective and innovative vocational training.